Analisis Premi dari Asuransi Pengangguran - Widana, I Nyoman; Jayanegara, Ketut (Jurnal Matematika; Vol 9 No 1 (2019)DO - 10.24843/JMAT.2019.v09.i01.p111, 2019)
Unemployment insurance is designed to overcome some of the financial problems faced by workers who have been involuntarily terminated from their jobs. The benefit insurance is financed based on the contributory from an employer, employee or government in recent times, some developing countries have been establishing unemployment insurance. This research aims to analyze the unemployment insurance products in Indonesia. Especially to analyze the financial viability of the product. The method used is the equivalence premium principle. Based on data sourced from BPJS Ketenagakerjaan and a claim rate of 10%, it is found that a premium rate of 5% of insured wages would support a benefit level of 50% of the wages for 43 weeks. This premium rate would also support 70% of the wages for 32 weeks. Meanwhile, the premium rate of 1% of the participant wages would guarantee a benefit level of 50% for 6 weeks.